Die Afrikaanse Verklarende Musiekwoordeboek - Grové, I.J. (Lexikos, 1995)
The Afrikaanse Verklarende MusiekwoordeboekDie Afrikaanse Verklarende Musiekwoordeboek The Afrikaanse Verklarende Musiekwoordeboek (1994) targets a gap in the literature available for Afrikaans-speaking music enthusiasts. It provides brief insight into basic aspects of music notation, proceeds to an alphabetical glossary, and lists some South African composers and their works. The last section is based largely (and without acknowledgement) on the Suid-Afrikaanse Musiekensiklopedie (1980-1986). The author has attempted to supply an Afrikaans equivalent for the internationally acclaimed American Harvard Dictionary of Music (latest edition 1986), and follows its format as a main source, again without acknowledgement. The procedure amounts to a somewhat arbitrary selection of facts, translated incorrectly at times and either misinterpreted or presented in a confusing manner at others. One consequence of such a procedure is undue emphasis on the American scenario at the cost of a potential reflection of the South African musical scene. Certain subjects and terms central to the science of music are omitted or underemphasized, often in favour of irrelevancies. The excessive length of an article like that on the history of music reveals a lack of balance in the publication, as well as essential deficiencies regarding a feasible and consistent system of cross-referencing. The mostly informal register of language verges on untidy unwieldiness. The astounding absence of collaborators can also be held to blame for the fact that the publication largely fails to contribute to the sparse Afrikaans literature covering the discipline of musicology.